Evaluation of Continuous Renal Replacement Therapy and Therapeutic Plasma Exchange, in Severe Sepsis or Septic Shock in Critically Ill Children - Aygün, Fatih (Medicina (Kaunas), 2019)
Background and objective: Severe sepsis and septic shock are life-threatening organ dysfunctions and causes of death in critically ill patients. The therapeutic goal of the management of sepsis is restoring balance to the immune system and fluid balance. Continuous renal replacement therapy (CRRT) is recommended in septic patients, and it may improve outcomes in patients with severe sepsis or septic shock. Therapeutic plasma exchange (TPE) is another extracorporeal procedure that can improve organ function by decreasing inflammatory and anti-fibrinolytic mediators and correcting haemostasis by replenishing anticoagulant proteins. However, research about sepsis and CRRT and TPE in children has been insufficient and incomplete. Therefore, we investigated the reliability and efficacy of extracorporeal therapies in paediatric patients with severe sepsis or septic shock. Materials and methods: We performed a multicentre retrospective study using data from all patients aged <18 years who were admitted to two paediatric intensive care units. Demographic data and reason for hospitalization were recorded. In addition, vital signs, haemogram parameters, and biochemistry results were recorded at 0 h and after 24 h of CRRT. Patients were compared according to whether they underwent CRRT or TPE; mortality between the two treatment groups was also compared. Results: Between January 2014 and April 2019, 168 septic patients were enrolled in the present study. Of them, 47 (27.9%) patients underwent CRRT and 24 underwent TPE. In patients with severe sepsis, the requirement for CRRT was statistically associated with mortality (p < 0.001). In contrast, the requirement for TPE was not associated with mortality (p = 0.124). Conclusion: Our findings revealed that the requirement for CRRT in patients with severe sepsis is predictive of increased mortality. CRRT and TPE can be useful techniques in critically ill children with severe sepsis. However, our results did not show a decrease of mortality with CRRT and TPE.